Moxibustion combined with chemotherapy inhibits gastric cancer growth by modulating the immunosuppressive microenvironment involving the Treg/IL-10/TGF-β1 axis - Wu, Yong; Ma, Li; Mao, Mengying; Leng, Yuling; Zhou, Xianyang; Xu, Heng; Ding, Yanqi; Hao, Wanrong; Dong, Wanhui; Zeng, Yonglei (Frontiers in Pharmacology, 2025)
BackgroundThe immunosuppressive microenvironment poses a major challenge in gastric cancer (GC) therapy. Moxibustion, based on the “Guben Peiyuan” theory, shows potential in oncology, but its immunomodulatory mechanisms in GC remain elusive.MethodsThis study integrated bioinformatics analysis with animal experiments. We analyzed pan-cancer expression and prognostic value of IL-10 and TGF-β1 via TCGA/GTEx databases. A mouse model of MFC gastric cancer was established to evaluate the effects of moxibustion (ST36, CV12, CV6, CV4), chemotherapy (5-FU), and their combination on tumor growth and the immune microenvironment.ResultsBioinformatics indicated that IL-10 and TGF-β1 were upregulated in GC, positively correlated with FOXP3+ Treg infiltration and poor prognosis. In vivo, the moxibustion + chemotherapy combination demonstrated the most potent tumor inhibition (inhibition rate: 45.9%). Mechanistically, the combination therapy exerted a “dual immunomodulatory effect” on the tumor immune microenvironment. It simultaneously suppressed immunosuppressive components, evidenced by reduced peripheral Tregs (7.02% vs. 3.91%), serum IL-10 (127.21 vs. 51.42 pg/mL) and TGF-β1 (547.84 vs. 266.82 pg/mL) levels, and downregulated Foxp3/TGF-β1 protein in tumors. Concurrently, it enhanced anti-tumor immunity, as evidenced by a significant increase in cytotoxic CD8+ T cell infiltration compared to the model group. Notably, the combined therapy elicited the most potent bidirectional immunomodulatory effect: it most effectively suppressed immunosuppressive components (reducing Tregs to 3.91% and serum TGF-β1 to 266.82 pg/mL) while simultaneously maintaining a robust CD8+ T cell response (22.8%), thereby achieving optimal overall remodeling of the tumor immune landscape.ConclusionThis study is the first to demonstrate that moxibustion synergizes with chemotherapy to inhibit gastric cancer growth through bidirectional remodeling of the immune microenvironment, simultaneously attenuating immunosuppression and boosting immune attack. Our findings provide a novel mechanistic insight into the integrated “Guben Peiyuan” and Western medicine strategy for GC.